Correlation between Peripheral Arterial Disease and Coronary Artery Disease in Bangladeshi Population- A Five Years Retrospective Study - Md Taimur, Syed Dawood; Chowdhury, Mashhud Zia; Hakim, Md Enamul (University Heart Journal, 2017)
Background: Peripheral arterial disease (PAD) is under diagnosed in primary care practices, yet the extent of unrecognized PAD in patients with coronary artery disease (CAD) is unknown. Objective: To assess the prevalence of previously unrecognized PAD in patients undergoing coronary angiogram and to determine the relationship between presence of PAD and severity of CAD. Material & Methods: This five years retrospective study was conducted at invasive lab of the department of Cardiology, Ibrahim Cardiac Hospital & Research Institute, Dhaka, Bangladesh from January 2010 to December 2014. Total 77 patients were included in this study. Study variables were age, sex, risk factors like hypertension, diabetes mellitus, dyslipidaemia, smoking habit and positive family history for ischemic heart disease, severity of coronary artery and peripheral artery disease. Results: Mean age was 56.83±13.64 years, Male mean age was 53.98±15.08 years and female mean age was 54.5±1.73years. Hypertension were detected in 55.8%, diabetes in 87%, dyslipidaemia in 81.8%, smoking habits in 88.3% and 58.4% had positive family history. After catheterization 88.3% had peripheral arterial disease and 71.4% had coronary artery disease. Out of 77 patients 52 had both coronary and peripheral arterial disease which was statistically significant (p<.014). Coronary angiogram revealed 28.6% (22) patients had triple vessel disease, 23.3% (18) had single vessel disease, 19.5% (15) had double vessel disease and 28.6% (22) were normal coronary arteries. Peripheral angiogram revealed 51.9% had superficial femoral artery disease, 24.7% had anterior tibial artery disease, 26% had posterior tibial artery disease, 15.6% had common iliac artery and common femoral artery disease and 2.6% had renal artery disease. Conclusion: There is a strong and definite correlation between coronary and peripheral arterial disease. We found that cardiovascular risk factors were in fact risk factors for both PAD and CAD. University Heart Journal Vol. 11, No. 2, July 2015; 79-84